Baamboozle’s Influence On Willingness To Communicate In English In Small Group Private Lessons (Journal of Namibian Studies : History Politics Culture, 2023)
This paper examines the results of an action research project on the use of Baamboozle as a gamification strategy to influence students’ willingness to communicate in English and their perception of the game. The study takes place in a context in which English does not play a fundamental part in the learning process during the early years of education. Therefore, a variety of relevant problems arise when learners need to work on their speaking skills. The sample of the research includes four private lesson students between 10 to 11 years old who usually work individually with the teacher, yet during the period the research took place, they worked together as one group. Considering this, several researchers have discovered that gamified activities play an essential role when teaching young learners since it provides unusual elements learners are not used to applying during class time. Seven interventions were carried out twice a week for three weeks to collect the data through observation, a Likert-type scale questionnaire, and a focus group. The data collected during the interventions suggested that Baamboozle is an effective tool to enhance willingness to communicate in an online teaching context.+++